Dermoscopy of Vitiligo and Other Hypopigmented Skin Lesions in Indian Patients: A Cross-Sectional Study - Sharma, Ananya; Khaitan, Binod; Gupta, Vishal; Ramam, M; Sahni, Kanika (Dermatology Practical & Conceptual, 2025)
Introduction: Non-vitiligo hypopigmented skin lesions may be close clinical mimickers of vitiligo, resulting in a diagnostic dilemma. Dermoscopic features of vitiligo have been studied, but those of other hypopigmentation disorders are not well-characterized.Objectives: We aimed to describe and compare the dermoscopic features of vitiligo and other hypopigmented skin lesions.Methods: A cross-sectional study including 105 vitiligo and 137 other hypopigmented skin lesions, including ash-leaf macules (n=17), nevus depigmentosus (n=16), post-inflammatory hypopigmentation (n=16), pityriasis alba (n=15), pityriasis versicolor (n=14), idiopathic guttate hypomelanosis (IGH) (n=14), lichen sclerosus (n=12), leprosy (n=9) and others. Dermoscopic findings were recorded by concordance of at least 2 qualified dermatologists.Results: Common dermoscopic findings in vitiligo were intermediate or ill-defined margins (96/105, 91.4%), and a complete absence of pigment network (70/105, 66.7%). Nevus depigmentosus lesions were mostly hypopigmented with a faint pigment network throughout the lesion. In 15/17 (88.2%) ash-leaf macules, a characteristic pattern of sharply demarcated areas of normal pigment network was seen within a depigmented lesion. Almost all lesions of IGH had a sharply defined margin with completely absent pigment network; discernible eccrine openings within the lesion were seen in 9/14 (64.3%). Dermoscopic findings of a complete absence of pigment network, perifollicular retention of pigment, presence of vascular pattern, loss of discernibility of eccrine openings within the lesion and lack of scaling were statistically significantly more common in vitiligo than other hypopigmented skin lesions (p<0.001).Conclusion: Vitiligo, nevus depigmentosus, ash-leaf macule and IGH have distinctive dermoscopic features. Dermoscopy can aid in the differential diagnosis of vitiligo and other hypopigmented skin lesions.